Journals and Monographs: An Italian perspective - Casalini, Barbara (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
When, some months ago, Prof. Dekeyser invited me to talk about the tendency to abandon Italian, as well as other European languages, in favour of the English language in the scientific periodicals sector, he obliged me to gather information on a sector different to the one in which I normally work. Indeed, since its beginnings, more than forty years ago, the raison d’être of Casalini Libri, the promotion and diffusion of Italian publications to libraries throughout the world, has always privileged the humanities, social sciences, history and art which reflect the prevalent character of Italian publishing. In order to have a sufficiently reliable picture of the situation, we have contacted a sample group of publishers of scholarly scientific periodicals of various types, obtaining information on the quantity of journals published, the languages used, possible total or partial changes in the choice of language over time, and the utilisation, present or future, of electronic resources. Subdividing the contacted publishers into 4 groups in order to illustrate certain lines of conduct indicates the results of this enquiry [1]. A separate section will then be dedicated to the developments in electronic publishing, with particular regard to the choice of language. The 4 groups are: · Academies · Small specialised scientific publishers · Large specialised scientific publishers · University Presses